2020
DOI: 10.1177/1010539520937100
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength and Mortality in Elderly Koreans: Evidence From the Korea Longitudinal Study of Ageing

Abstract: Despite substantial research on numerous aspects of health in the elderly, past studies that examined the association between handgrip strength and mortality have been conducted with samples drawn mostly from Caucasian populations, and little is known about whether similar trends are found in non-Western contexts such as Korea. The present study drew data from KLoSA (Korean Longitudinal Study of Aging), a nationally representative sample of middle-aged adults, and followed up for a decade. Results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Coronavirus disease 2019 (COVID- 19) is also considered in the present work. Prior studies have pointed out that COVID-19 has changed daily life because of restrictions due to the risk of infection [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) is also considered in the present work. Prior studies have pointed out that COVID-19 has changed daily life because of restrictions due to the risk of infection [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 Handgrip strength has been found to relate to physical function, mortality rate, and health-related quality of life. 3,[7][8][9][10][11][12] However, a prior study found no difference in the health-related quality of life of older women according to HGS, 4 suggesting that differences may exist in the relationship between HGS and health-related quality of life according to sex. The relationship between HGS and health-related quality of life may also vary depending on the subdomains of healthrelated quality of life.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, evidence suggests that psychosocial factors matter for preventing or delaying dementia and AD. In general, the weight of evidence indicates that physical and cognitive functioning in older adults are closely interwoven [40]. Nevertheless, a considerable number of etiologic pathways from handgrip strength, which Clouston et al [2] suggested as one of most effective measures for physical frailty, toward dementia in Korea remain unclear, and an empirical analysis using longitudinal methods is therefore warranted.…”
Section: Determinants Of Cognitive Impairmentmentioning
confidence: 99%